Translational regulation by Hfq–Crc assemblies emerges from polymorphic ribonucleoprotein folding. (12th December 2022) - Dendooven, Tom; Sonnleitner, Elisabeth; Bläsi, Udo; Luisi, Ben F
Abstract: The widely occurring bacterial RNA chaperone Hfq is a key factor in the post‐transcriptional control of hundreds of genes in Pseudomonas aeruginosa . How this broadly acting protein can contribute to the regulatory requirements of many different genes remains puzzling. Here, we describe cryo‐EM structures of higher order assemblies formed by Hfq and its partner protein Crc on control regions of different P. aeruginosa target mRNAs. Our results show that these assemblies have mRNA‐specific quaternary architectures resulting from the combination of multivalent protein–protein interfaces and recognition of patterns in the RNA sequence. The structural polymorphism of these ribonucleoprotein assemblies enables selective translational repression of many different target mRNAs. This system elucidates how highly complex regulatory pathways can evolve with a minimal economy of proteinogenic components in combination with RNA sequence and fold. Synopsis: Bacterial RNA chaperone Hfq and cofactors regulate numerous cellular processes at the level of mRNA translation. Here, cryo‐EM structures of Hfq in complexes with mRNA control elements and the carbon catabolite repression (CCR) co‐repressor Crc reveal a basis for specificity and individually tuned responses. A combination of RNA sequence and two proteins can generate the diversity required to regulate many genes with adequate sequence specificity, as exemplified by the amiE, estA, and rbsB transcripts. Interactions of Hfq and Crc with sequence motifs and structural elements in different mRNA targets and diverse protein‐to‐protein interfaces result in different quaternary structures. The multi‐step assembly process appears highly cooperative and may compete kinetically with translation initiation to silence the targeted transcripts. Abstract : A combination of RNA sequence and Hfq/Crc binding generates different quaternary structures needed for specific regulation of diverse pool of target genes.